IDENTIFIKASI MOLEKULAR DAN MORFOLOGIS UDANG AIR TAWAR ANGGOTA GENUS MACROBRACHIUM (DECAPODA, PALAEMONIDAE) DARI HILIR SUNGAI PAKERISAN, BALI - Natasya Nur Musrifa (Scripta Biologica, 2019)
Indonesia with an area of tropical waters 5.4 billion km2 depend on the largest source of foreign exchange earnings derived from prawns. Freshwater prawns of the genus Macrobrachium shown a wide distribution and high economic value. Bali has potential for high freshwater prawns diversity with an area 10,000 Ha of cultivation. Pakerisan river is one of Bali’s rivers with high population, so affected prawns ecosystem in habitat. The study was conducted to determine the diversity of freshwater prawn species belonging to genus Macrobrachium based on morphological identification and molecular analysis with 16S mitochondrial gene from the downstream of Pakerisan river. Sampling was administered by Gianyar Research Team in March 2015. Initial identification and determination of morphological characters was done. Afterwards, identification of prawns molecular characters using primers 16Sar and 16Sbr were analyzed by DNAStar software, MESQUITE, DNA Sequence Polymorphism 5.10, and MEGA 7.0.21. The results based on morphological identification of individual CR1 and CR2 that was: second pereiopod had longer carpus than merus and chela, epistome split into 2 round anterior lobes, rostral formula: 3+5/3, and 2 pairs of spines on parallel telson. Supported by molecular identification DNA fragment length sequencing were 561bp. BLAST analysis similarity 99%, average genetic distance 0.24%, and bootstrap value 100% in reconstruction with Neighbor-Joining phylogeny tree showed monophyletic group with seven samples sequence Macrobrachium lancesteri from NCBI GenBank. So morphological and molecular identification was declared CR1 and CR2 individuals included to species Macrobrachium lanchesteri.